Factores de riesgo para accidentes laborales en los talleres de carpintería del barrio Piuntza, parroquia Guadalupe. Periodo 2015 - Wachapa Ushap, Carmen Lorena (2015)
The objective of this research work named "Risk Factors for Labor accident” in the Carpentry Workshops in Piuntza neighborhood, in Guadalupe town, during the year 2015". 31 workers with the 9 different carpentry workshops from Piuntza neighborhood, located in the southern region from Ecuador was considered to the development of this research work. The instruments taken into account in this process were the survey as well as an observation guide in order to determine the defining factors in each one of the nine carpenters. The design of the study was epidemiological, and the types of observation used were: prospective, transversal, bibliographic and empiric. The results among these were: The Age of the workers in a 22.58% are under 19 year old, and male predominate in a 77.42%. The 100% resides in the same neighborhood. The educational level in its majority is secondary with the 51.61%. Among the most Risky Dominance in the workers the next ones were identified: The Ergonomic Risk with the 100%. Chemical Risk in an 85.18%, Physical Risk in an 80.55%, Risk Architectural with the 100% due to the absence of caveat signs, followed by electrical and mechanical factors. The most common occupational accidents suffered by these workers, with the mayor percentage are the punctures with nails in a 54.84%, beating in a 45.16%, cuts with a 25,81%, and with less percentages are; the electrical contacts, toxic substances contact and amputations. It was concluded that: The 9 Carpentry workshops presented labor risks, and the main ones are: ergonomic, chemical, architectural, mechanical, electrical, and physical risks. And the most common risks are: the punctures with nails, bruises and cuts, which are produced by the direct contact with the carpentry machines as well as the tools